Pendampingan Soft Skill Awareness: Komunikasi Efektif bagi Siswa (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Effective communication remains challenging for many students, including those at MAN 2 Kerinci, who are passive in discussions and struggle to express ideas. This community service program aimed to improve students’ awareness and communication skills using an experiential learning approach through interactive lectures, discussions, simulations, and role play. Thirty students and several parents participated as partners. Evaluation was conducted through pretest-posttest questionnaires and direct observation. The results indicate improved students’ communication skills, such as increased confidence, structured idea delivery, and empathetic interaction. A participatory approach and parental involvement were key to the program’s success. This structured training proves effective in enhancing students’ soft skills.
Keywords: komunikasi; Pelatihan dan pendampingan; soft skill